Digital Distractions or Digital Engagement? Analyzing the Effect of Mobile Devices in the Classroom - Dr. Najma Begum; Zeeshan Ahmad (Journal of Religion and Society, 2025)
The current device proliferation has greatly transformed the traditional educational environment especially in the secondary and higher learning educational settings where the ownership and usage of devices by students is very rampant. This research exercise examines the two-fold impact of mobiles phones in the classroom, the question being whether mobiles phones are digital distractions or digital engagement tools in the classroom. Data were gathered using mixed-methods approach using student and teacher surveys, classroom observations, and interviewing of students and teachers in urban and semi-urban educational institutions. The quantitative analysis, ANOVA and regression showed that there was a considerable variance in the performance levels that was connected to usage pattern of the mobile devices. Students with educational use of mobile phones, accessing digital content, taking part in quizzes, and working collaboratively, showed an increase in academic performance than those who often used them to entertain themselves or use social media. Qualitative data were also analyzed in a thematic fashion to point out such mediating factors of student engagement as self-regulation and classroom culture and institutional digital policy. The results highlight the fact that mobile devices are not necessarily disruptive but what matters is the device integration within pedagogy. Digital norms, teacher guidance, and active learning strategies in classrooms that were also clear led to better results when it comes to mobile technology being used to engage students and encourage them to pay more attention. Conversely, settings with unstructured digital incorporation typically made a distinction between more distraction and low scholastic performance. The paper endorses a reasonable and pedagogically substantive assimilation of mobile technology that encompasses self-regulated learning, teacher ready, and institutional policy change. The insights are vital to teachers, administrators and policy makers who wish to transform mobile technology that has been considered as a classroom problem to one that can be used to further learning and engage. Keywords: Mobile Devices, Digital Distraction, Student Engagement, Classroom Learning, Self-Regulated Learning, Cognitive Load, Mobile Learning Integration, Academic Performance, Education Technology, Secondary, Higher Education